Relationship between handedness and joint involvement in rheumatoid arthritis - Yaku, Ai (Sci Rep, 2016)
Rheumatoid arthritis (RA) is characterized by autoimmune chronic joint inflammation, which is worsened by mechanical stress. It is still inconclusive whether joints on the right side or the dominant side get more damaged in RA since the limited number of patients analyzed in the previous study had made it difficult to separately analyze right-handed and left-handed patients. Here, we enrolled 334 RA patients, the biggest number of patients in studies to address this issue and separately analyzed right-handed and left-handed patients. As a result, we observed that joints on the dominant side got clinically and radiologically more involved in the right-handed patients (p ≤ 0.0030). Importantly, this tendency was also seen in the left-handed patients, while it was not statistically significant due to the small sample size. This tendency was observed in each component of clinical or radiological involvement. Thus, handedness influences the laterality of clinical and radiological joint involvement in RA.